2023
DOI: 10.1101/2023.09.04.23295005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicentric validation of a Multimorbidity Adjusted Disability Score to stratify depression-related risks using temporal disease maps

Rubèn González-Colom,
Kangkana Mitra,
Emili Vela
et al.

Abstract: In the EU project TRAJECTOME, we used a novel methodology to identify temporal disease maps of depression and highly prevalent co-occurring disease conditions. This information was combined with disability weights established by the Global Burden of Disease Study 2019 to create a depression-related health risk assessment tool, the Multimorbidity Adjusted Disability Score (MADS). MADS was used to stratify over one million cases from three different cohorts and evaluate the impact on utilisation of healthcare re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A second field of research interest is the potential evolutions of AMG incorporating information on patients' disease trajectories [42,43]. A recent study [44] revealed that this approach provides promising prospects to support tailored epidemiological studies, enabling targeted interventions for particular patient groups. Additionally, integrating the probabilities of disease-disease co-occurrence into the evaluations could assist in assessing the risk of developing certain disease conditions.…”
Section: Evolution Of the Catalan Ogp During Jadecarementioning
confidence: 99%
“…A second field of research interest is the potential evolutions of AMG incorporating information on patients' disease trajectories [42,43]. A recent study [44] revealed that this approach provides promising prospects to support tailored epidemiological studies, enabling targeted interventions for particular patient groups. Additionally, integrating the probabilities of disease-disease co-occurrence into the evaluations could assist in assessing the risk of developing certain disease conditions.…”
Section: Evolution Of the Catalan Ogp During Jadecarementioning
confidence: 99%